Uji Potensi Hepatoprotektor Ekstrak Daun Kelor (Moringa Oleifera L.) Terhadap Hati Tikus Putih (Rattus Norvegicus L.) yang Diinduksi Etilen Glikol - Muhammad Wahyu Hidayat; Syukriah Syukriah; Husnarika Febriani (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2026)
Consumption of ethylene glycol–containing drugs can cause liver damage. This study aimed to evaluate the hepatoprotective potential of Moringa leaf extract (Moringa oleifera L.) on AST and ALT levels, liver morphology, hepatosomatic index, and liver histology in ethylene glycol–induced white rats (Rattus norvegicus L.). A Completely Randomized Design (CRD) was used with 20 male rats divided into five groups: normal control, ethylene glycol control, and three treatment groups (150, 300, and 450 mg/kg BW). Ethylene glycol was administered for 30 days, while the extract was given for 20 days. Blood samples were collected on day 31. Data were analyzed using One Way ANOVA and Duncan’s test. The results showed significant hepatoprotective effects (P = 0.000). AST and ALT levels in the treatment groups differed significantly from the normal control. Liver morphological changes were observed in both control and treatment groups. The hepatosomatic index, number of normal hepatocytes, and central vein diameter also showed significant differences. In conclusion, Moringa leaf extract demonstrates hepatoprotective potential by reducing AST and ALT levels, improving liver morphology, increasing normal hepatocytes, and decreasing central vein diameter, with the optimal dose at 450 mg/kg BW